Effects of street lights on the web site selection of two species of spiders Neoscona theisi (Walckenaer, 1841) and Leucauge decorata (Blackwall, 1864) - Nending Muni; Abhinav Mishra; Neelkamal Rastogi (Dera Natung Government College Research Journal)
Neoscona theisi and Leucauge decorata are two orb-web weaving spiders that are generally found between the branches of the bushes, the shrubs and the trees. Ever since the artificial lightening of the streets became the norm in modern cities, it became a major component of urbanization which influences the overall biodiversity all around the world. This study concentrates mainly on the web-site selection based on the presence and the absence of the street light which may influence the prey abundance at that particular area. The spider species studied are found in higher abundance on the trees that are in the close proximity to the streetlights. The majority of the arthropod prey species are dipterans. Other arthropods prey belonging to Orthoptera, Coleoptera, Hymenoptera, Lepidoptera and Odonata are also found on the webs of these two spider species on the selected plant species in which they were studied.